Yovi Birawanto's Creative Process and Social Life in the Creation of Musical Works - Putri Nesha Ryuko; Kurnia Rachmawati; Dicky Rachmat Pauji (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the creative process and social background of Indonesian independent musician Yovi Birawanto in producing his musical works. Music, particularly song lyrics, is not merely an aesthetic expression but also a medium that reflects the artist’s interaction with social realities. This research aims to describe how Yovi’s social experiences influence his creative process, to explain the stages of creativity involved, and to identify the dominant social themes represented in his songwriting. Employing a qualitative approach, the study utilizes in-depth interviews, lyric analysis, and live performance observation. The findings reveal that Yovi’s creative works emerge from collective and contextual experiences rather than personal sentimentalism. His songwriting is strongly influenced by shared emotional realities, such as human vulnerability, existential anxiety, and the need for emotional space within contemporary social life. These themes are articulated through reflective and metaphorical language that resonates with broader public experiences. Furthermore, the creative process follows four integrated stages: preparation through idea collection based on social observation, incubation within moments of reflective silence, illumination marked by the sudden emergence of musical or lyrical ideas, and verification through collaborative refinement with the band. Performance observation confirms that live performance functions as the final phase of verification, enabling emotional dialogue between the artist and the audience. In conclusion, Yovi Birawanto’s musical works operate as a form of social discourse in which creativity becomes a dialogic interaction between the artist, social environment, and listeners, positioning independent music as a meaningful medium of popular literary expression.